EdTech KISK: Studijní profilace Technologie ve vzdělávání - Černý, Michal; Tulinská, Hana (Masaryk University Press, 2019)
Title in English: EdTech KISK: Study specialization of technology in education. The publication presents the study profile of technology in education within the study of information sciences and librarianship. It offers a synthetizing view of the development and mission of the entire study profile, but also the changes in its staffing and publishing activities. It provides a comprehensive view of critical thinking about how to talk about technology in education to the academic community, but above all, to students. It seeks a crucial aspect of the current situation and at the same time, opens prospects for further development. It leads the reader to a view of research - the pedagogical group that is unique within the Czech environment for its strong roots in topics such as information education, online courses, research in the educational environment or the use of virtual reality for collaborative tasks.